Enhancing Telemedicine Communication for Improved Outpatient Pediatric Trauma Care - Nariman Mokhaberi; Benjamin Schoof; André Strahl; Konrad Reinshagen; Kristofer Wintges (MDPI AG, 2024)
Introduction. Pediatric traumatology is a complex field that requires a comprehensive understanding of physeal development, remodeling potential, and the ossification process in order to ensure appropriate patient treatment. The objective of this study was to assess the willingness of practicing physicians to participate in a telemedicine collaboration aimed at enhancing the exchange between the outpatient and inpatient sectors and promoting the digitalization of the pediatric sector. This is in response to the growing significance of digitalization in the medical field. Methods. A survey consisting of 15 items was sent to 800 practicing trauma surgeons, pediatric surgeons, and pediatricians within a 100 km radius of Hamburg, Germany. The survey included questions about the respondents' professional experience and telemedicine experience, as well as inquiries about possible telemedicine collaborations. Results. The response rate was 19.3%. Less than half of the participants already used telemedicine in daily practice. In general, 75% of respondents expressed an interest in collaborating with the inpatient sector. The most common reasons for hospital referral were the need for surgery, inadequate treatment of children in practice and co-assessment. The majority were in favor of flexible communication, either via video telephony, imaging applications like or messaging applications. Conclusions. The study revealed a high level of interest in telemedicine collaboration. Information exchange should be tailored to individual needs, with practitioners requiring a versatile and personalized approach that includes imaging. Strict enforcement of data protection regulations is essential. Further research is needed to evaluate the effectiveness of telemedicine collaboration in the treatment of pediatric trauma in both hospital and outpatient settings.